Is Weekly Supplementation of Vitamin D Favorable for Treatment of Osteoporosis in Postmenopausal Women? - Budak, Mehmet Şükrü; Akgöl, Sedat; Önen, Şahin; Erdem, Selami; Kahyaoğlu, Serkan; Kanat Pektaş, Mine (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVE: The present study aims to determine whether once weekly supplementation of vitamin D and alendronate is efficient and safe for treatment of postmenopausal osteoporosis. STUDY DESIGN: Group I (42 women with postmenopausal osteoporosis) received daily supplementation of calcium (1000 mg) and vitamin D (880 IU) while group II (42 women with postmenopausal osteoporosis) had weekly supplementation of vitamin D (2800 IU) along with weekly treatment of alendronate (70 mg). RESULTS: Group I had significantly lower lumbar spine T-scores before and after treatment. Post-treatment lumbar spine T-scores and femur neck T-scores were significantly higher with respect to pre-treatment scores in both study groups. The alterations in lumbar spine and femur neck T-scores were statistically similar in both group I and group II. CONCLUSION: Once weekly administration of vitamin D and alendronate is an effective and safe option of treatment for women who cannot take calcium supplements for postmenopausal osteoporosis.